Nanometer bacterial cellulose conductive filler as well as preparation method and application thereof
By reducing the deposition of metal nanocopper/silver particles in situ, the problem of poor binding force between nanoparticles and bacterial cellulose is solved, and the excellent performance and simplified process of conductive composite film materials are achieved. Various application areas.
Patent Information
- Application Number
- CN202411277484.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, when preparing bacterial cellulose conductive composite film materials, the binding force between nanoparticles and bacterial cellulose matrix is poor, and the nanoparticles are prone to agglomeration and cannot be evenly dispersed, which increases the cost of materials and preparation complexity, and the morphology and size of nano-gold particles is difficult to Accurate control, high production cost.
In situ reduction process is used to uniformly deposit metal nanocopper/silver particles in the three-dimensional network structure of bacterial cellulose. Through pretreatment and preparation of dispersion, the uniform dispersion of nanobacterial cellulose conductive filler is ensured, and thermal curing is combined with polymer materials. Prepare nanobacterial cellulose-based conductive composite membrane materials.
The excellent conductivity and mechanical properties of nanobacterial cellulose conductive composite film materials are achieved, the process flow is simplified, the production cost is reduced, and it is suitable for antistatic, electromagnetic shielding and stretchable electrode materials.
Smart Images

Figure CN119119589A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing conductive composite materials, and in particular relates to a nano bacterial cellulose conductive filler and a preparation method and application thereof. Background Art
[0002] With the rapid development of the electronics industry, flexible composite membrane materials have been widely used in the fields of communications, transportation, electronics, aviation, and construction industries. Among them, conductive composite membrane materials have a wide range of applications in antistatic, electromagnetic shielding, sensing, and electrode materials. Bacterial cellulose (BC) is a natural cellulose synthesized by certain bacteria. It has a unique interconnected and adjustable three-dimensional network structure of ultrafine nanofibers. In addition, it also has excellent physical and chemical properties such as high water retention, high purity and high crystallinity, porosity, large specific surface area, high elastic modulus and tensile strength. Due to its unique three-dimensional network structure and nanoscale fibers, it is widely used in composite membrane materials, medical, electronic and intelligent textile biomaterials, electrochemical energy storage and other fields.
[0003] Bacterial cellulose conductive composite film materials provide excellent electrical conductivity and excellent mechanical properties, and have broad application prospects in the field of flexible electronics. At present, the most commonly used method for preparing high-performance bacterial cellulose conductive composite film materials is the nanomaterial composite modification process, that is, using bacterial cellulose as a template material, using its excellent adsorption properties to allow external ions to enter the three-dimensional network structure, while a large number of electronegative hydroxyl groups and ether bonds are used as effective reaction sites, and the introduced ions are fixed on the surface of nanofibers, and nanocomposites with different structural morphologies are formed in situ through chemical precipitation and oxidation-reduction reactions. At the same time, the ultrafine nanoscale three-dimensional network structure and nanoscale pore size of bacterial cellulose can provide internal channels for the introduction of composite materials. Therefore, using bacterial cellulose as a matrix material can control the synthesis of new functional nanocomposites with specific morphology, size and excellent performance. However, the bacterial cellulose conductive composite film materials currently prepared by the nanomaterial composite modification process generally have poor binding force between nanoparticles and the bacterial cellulose matrix, and the nanoparticles are easy to agglomerate and cannot be evenly dispersed. Additional reducing agents or stabilizers need to be added, which increases material costs and may also affect the biocompatibility and stability of the material. In addition, the control of the morphology and size of nanoparticles requires precise control and technology, including material pretreatment and adjustment of reaction conditions, which increases the complexity and technical difficulty of the preparation process.
[0004] In order to achieve the preparation of bacterial cellulose conductive composite film materials with excellent performance, patent CN106299385A publicly reported that bacterial cellulose was used as a carbon source, soaked in urea solution, freeze-dried and carbonized to obtain nitrogen-doped carbonized bacterial cellulose, and then in-situ reduction of loaded nano-platinum particles on the fiber to prepare nitrogen-doped carbonized bacterial cellulose loaded nano-platinum electrode materials. However, the surface of nitrogen-doped carbonized bacterial cellulose prepared by this process has obvious agglomeration of nano-platinum particles, poor dispersion performance, and complex production process, which is not conducive to large-scale production. Patent CN112094437A publicly reported that bacterial cellulose, aniline, DMF, water, concentrated hydrochloric acid and ammonium sulfate solution were mixed and heated to obtain bacterial cellulose / polyaniline composite film, and then the bacterial cellulose / polyaniline composite film was immersed in a nano-gold aqueous solution prepared by the reaction of sodium citrate and chloroauric acid and fully stirred to prepare a bacterial cellulose / polyaniline / gold nanoparticle composite material. However, the morphology and size of the gold nanoparticles in the bacterial cellulose / polyaniline / gold nanoparticle composite material prepared by this process are difficult to accurately control, and the loading amount of gold nanoparticles is low. The use of chloroauric acid and the like significantly increases the production cost.
[0005] Therefore, it is necessary to develop a method for preparing bacterial cellulose conductive composite membrane materials with excellent performance, simple process, low cost and large-scale production. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a nano bacterial cellulose conductive filler and a preparation method and application thereof, wherein the method specifically comprises the following steps: pre-treating and purifying bacterial cellulose to prepare a bacterial cellulose dispersion, adding a reducing agent to the bacterial cellulose dispersion to disperse the dispersion uniformly, then adding a mixed solution of a metal silver ion or copper ion solution, a dispersant and a stabilizer to obtain a nano bacterial cellulose conductive filler, uniformly dispersing the filler in an organic solvent, and finally adding the filler to a polymer material, and thermally curing the filler to prepare a nano bacterial cellulose-based conductive composite film material. The present invention uses bacterial cellulose as a matrix material to introduce metal nano copper / silver particles, effectively deposits the metal nano copper / silver particles in its nanofiber three-dimensional network structure, realizes uniform distribution of the metal nano copper / silver particles in the bacterial cellulose matrix, and finally adds the filler to a polymer material to prepare a nano bacterial cellulose-based conductive composite film material, which can be used for antistatic materials, electromagnetic shielding materials, stretchable electrode materials, and the like.
[0007] A nano bacterial cellulose conductive filler is prepared by using the nano bacterial cellulose as a matrix material and in-situ reduction deposition of nano copper particles or nano silver particles on the three-dimensional network structure of the nano bacterial cellulose.
[0008] The preparation method of the nano bacterial cellulose conductive filler specifically comprises the following steps:
[0009] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion: After purifying the nano bacterial cellulose, modify and disperse it to obtain a pretreated nano bacterial cellulose dispersion;
[0010] (2) mixing the alkaline solution and the reducing agent and stirring them uniformly to obtain a mixed solution, adding the mixed solution to the pretreated nano bacterial cellulose dispersion and stirring them uniformly to obtain a nano bacterial cellulose reduced solution;
[0011] (3) under constant temperature conditions, mixing and stirring a copper ion solution or a silver ion solution, a dispersant and a stabilizer to obtain a mixed solution, then dropping the mixed solution into a nano bacterial cellulose reduction solution, stirring and reacting for a period of time, and in-situ reducing the nano bacterial cellulose on the nano bacterial cellulose matrix to obtain nano copper particles or nano silver particles;
[0012] (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0013] in:
[0014] In the step (1), the purification process of the nano bacterial cellulose is as follows: the nano bacterial cellulose is fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it is immersed in an alkaline solution, heated and boiled to wash out the culture medium and bacteria remaining inside the particles, then rinsed with an acid solution for neutralization, and finally rinsed with deionized water to obtain the purified nano bacterial cellulose;
[0015] The alkaline solution is a 0.05-0.2 mol / L NaOH solution, heated at 75-95°C, and boiled for 60-120 min;
[0016] The acid solution is a 0.1-0.5 wt. % CH3COOH solution, which is rinsed to a pH of 6.8-7.2.
[0017] In the step (1), the modified dispersion process of the purified nano bacterial cellulose is as follows: adding the purified nano bacterial cellulose into a solvent for dispersion treatment, and then adding a modifier for chemical modification to obtain a pretreated bacterial cellulose dispersion;
[0018] The solvent is one or two of deionized water, ethanol, and isopropanol. When two solvents are selected, the ratio between the two solvents is arbitrary; the mass ratio of cellulose to solvent is 1: (10-100);
[0019] The dispersion treatment method is a mixed treatment method of one or more of mechanical stirring, ultrasonic dispersion, high-pressure homogenization, and centrifugal dispersion, and the dispersion treatment time is 0.5 to 3.0 hours;
[0020] The modifier is selected from one or more of dopamine, 3-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-β-(aminoethyl)γ-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)γ-aminopropylmethyldiethoxysilane. When multiple modifiers are mixed, the multiple modifiers can be in any proportion. The volume ratio of the modifier to the solvent is 1:(25-50), and the modification time is 6-12h.
[0021] The concentration of the pretreated bacterial cellulose dispersion is 0.1-40 wt.%.
[0022] In the step (2), the alkaline solution is a sodium hydroxide solution or aqueous ammonia, the concentration of the sodium hydroxide solution is 0.05-0.15 mol / L, and the concentration of the aqueous ammonia is 0.5 mol / L.
[0023] In the step (2), the reducing agent is one or two of sodium borohydride, glyoxylic acid, glucose, potassium sodium tartrate, L-ascorbic acid and sodium citrate. When two reducing agents are selected, the molar ratio of the two is 1:1; the concentration of the reducing agent is 0.02-0.1 mol / L;
[0024] In the step (2), the volume ratio of the pretreated nano bacterial cellulose dispersion, the alkaline solution and the reducing agent is 5:(1-5):(1-10), and the stirring time is 30-60 minutes.
[0025] In the step (3), the constant temperature condition is 10-60° C., the concentration of the copper ion solution or the silver ion solution is 0.02-0.1 mol / L, and the volume ratio of the copper ion solution or the silver ion solution to the nano bacterial cellulose reducing solution is 1:(1-5); wherein the copper ion solution is selected from one of a copper sulfate aqueous solution, a copper chloride aqueous solution and a copper nitrate aqueous solution, and the silver ion solution is a silver nitrate solution or a silver amine complex solution;
[0026] The silver amine complex solution is one of a silver amine oxalate complex solution, a silver amine acetate complex solution, a silver amine malonate complex solution, a silver amine tartrate complex solution, a silver amine citrate complex solution and a silver amine neodecanoate complex solution.
[0027] In the step (3), the amount of the dispersant is 0.5 to 1.0 times the mass of the nano bacterial cellulose, and is selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide and sodium dodecylbenzene sulfonate. When multiple dispersants are mixed, the multiple dispersants are in any proportion.
[0028] In the step (3), the stabilizers are ethanol and polyethylene glycol 200, both of which are analytically pure; the amount of stabilizer added is 50-100 mL of ethanol and 10-20 mL of polyethylene glycol 200 per liter of reducing agent; the mixed solution is added to the nano bacterial cellulose reducing solution through a peristaltic pump at a speed of 100 rpm, and the reaction time is 30-120 min.
[0029] The application of the above-mentioned nano bacterial cellulose conductive filler is specifically to use it in the preparation of nano bacterial cellulose-based conductive composite film materials, including nano bacterial cellulose-based antistatic films, nano bacterial cellulose-based electromagnetic shielding films and nano bacterial cellulose-based stretchable electrode materials.
[0030] The method for preparing the above-mentioned nano bacterial cellulose-based conductive composite film material specifically comprises the following steps:
[0031] The nano bacterial cellulose conductive filler is added into a solvent and dispersed evenly, and then added into a polymer material, stirred evenly and then thermally cured to obtain a nano bacterial cellulose-based conductive composite film material.
[0032] in:
[0033] The mass ratio of the nano bacterial cellulose conductive filler to the solvent is (0.1-1.0):10; the solvent is selected from one or two of ethanol, isopropanol, cyclohexane and ethyl acetate, all of which are analytically pure. When two solvents are selected, the two solvents are in any ratio; the dispersion treatment method is a mixed treatment of one or more of mechanical stirring, ultrasonic dispersion, high-pressure homogenization and centrifugal dispersion, and the dispersion treatment time is 0.5-1.0h.
[0034] The polymer material is one of a release agent, a pressure-sensitive adhesive and a hardening resin; the release agent is a silicone oil release agent, the pressure-sensitive adhesive is one of an organic silicone pressure-sensitive adhesive, an acrylate pressure-sensitive adhesive and a rubber pressure-sensitive adhesive, and the hardening resin is one of an epoxy resin, an acrylic resin, a polyurethane resin, an acrylic modified polyurethane resin and a propylene oxide resin; the stirring time is 0.5 to 1.0 h.
[0035] The thermal curing is specifically performed in an oven at a temperature of 150 to 200° C. for a curing time of 1 to 5 minutes.
[0036] The surface resistance of the nano bacterial cellulose based antistatic film is 10 5 ~10 8 Ω; the shielding effectiveness of the nanobacterial cellulose-based electromagnetic shielding film is 45-60dB; the conductivity of the nanobacterial cellulose-based stretchable film electrode material is 0.1-0.5S / m, the specific capacitance is 400-800F / g at a current density of 1A / g, and the stress-strain is 80-150MPa.
[0037] The key points of the technology of the present invention are:
[0038] 1. The in-situ reduction process is used to uniformly deposit the metal nano copper / silver particles in the three-dimensional nano-network structure of bacterial cellulose. The production process is simple, and the metal nano copper / silver particles have good dispersibility, avoiding the agglomeration phenomenon, and have a strong bond with the bacterial cellulose matrix and are not easy to fall off. The nano bacterial cellulose conductive filler is added to the polymer material, and the obtained nano bacterial cellulose-based conductive composite film material has excellent conductive properties and can be used in antistatic materials, electromagnetic shielding materials and other fields, with excellent antistatic and electromagnetic shielding properties.
[0039] 2. The nano bacterial cellulose-based conductive composite film material prepared by the present invention utilizes the characteristics of bacterial cellulose such as ultra-fine three-dimensional nano-network structure, excellent high elastic modulus and tensile strength to improve the mechanical properties of nano conductive composite materials. The nano bacterial cellulose conductive filler is added to the polymer material and can be applied to the preparation of stretchable electrode materials. The prepared nano bacterial cellulose-based stretchable thin film electrode material has excellent electrical properties and mechanical tensile properties.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The metal nano copper / silver particles prepared by in-situ reduction in the present invention have an easily controllable shape and size, can be uniformly loaded on the bacterial cellulose matrix, have strong binding force, and have excellent conductive properties.
[0042] 2. The bacterial cellulose used in the present invention has ultra-fine three-dimensional network structure, excellent high elastic modulus and tensile strength and other characteristics, which can significantly improve the mechanical properties of the conductive composite material.
[0043] 3. The nano bacterial cellulose-based conductive composite film material of the present invention has excellent performance, high stability, simple synthesis process, low production cost, is environmentally friendly, and is conducive to large-scale production.
[0044] 4. The preparation method and application of the nano bacterial cellulose conductive filler and its composite film material provided by the present invention can effectively overcome the common problems of poor binding force between nanoparticles and bacterial cellulose matrix and easy agglomeration of nanoparticles and inability to disperse evenly when preparing bacterial cellulose conductive composite materials using the current nanomaterial composite modification process.
[0045] 5. The present invention adopts an in-situ reduction process, takes bacterial cellulose as the matrix, and deposits metal nano-copper / silver particles on its ultra-fine three-dimensional nano-network structure, thereby giving it excellent electrical properties while retaining its good mechanical properties. The prepared nano-bacterial cellulose-based conductive composite film material can be used in the fields of antistatic materials, electromagnetic shielding materials, and stretchable electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Schematic diagram of the preparation principle of the nano bacterial cellulose conductive composite film material of the present invention;
[0047] Figure 2 Schematic diagram of the structure of the nano bacterial cellulose conductive composite film material of the present invention. DETAILED DESCRIPTION
[0048] The following examples are provided to further understand the present invention better, are not limited to the best mode, and are not intended to limit the content and scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts, all falls within the protection scope of the present invention. If no specific experimental steps or conditions are indicated in the examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0049] Example 1
[0050] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0051] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0052] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0053] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropyltrimethoxysilane was added and modified for 12 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0054] (2) 100 mL of 0.05 mol / L sodium borohydride solution and 10 mL of 0.1 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 45 min to obtain a nano bacterial cellulose reduced solution.
[0055] (3) In a constant temperature water bath at 30°C, 100 mL of 0.05 mol / L silver nitrate solution, 0.5 g of polyvinyl pyrrolidone, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of sodium borohydride solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 30 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0056] (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0057] Nano bacterial cellulose conductive filler is used to prepare nano bacterial cellulose based conductive composite film material. The schematic diagram of the preparation principle is shown in Figure 1 As shown, the structural diagram is as follows Figure 2 As shown, the preparation method comprises the following steps:
[0058] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL of ethanol and isopropanol, and stirred and dispersed for 1h; the dispersed solution was added to the silicone pressure-sensitive adhesive, stirred and dispersed for 1h, and coated on a PET substrate using a wire rod coating process, and the coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based antistatic film. The surface resistance of the nano bacterial cellulose-based antistatic film is 1.2×10 5 Ω.
[0059] Example 2
[0060] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0061] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0062] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0063] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropylmethyldiethoxysilane was added and modified for 6 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0064] (2) 100 mL of 0.075 mol / L L-ascorbic acid solution and 15 mL of 0.5 mol / L ammonia water were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 60 min to obtain a nano bacterial cellulose reduced solution.
[0065] (3) In a constant temperature water bath at 30°C, 100 mL of 0.075 mol / L silver nitrate solution, 0.5 g of hexadecyltrimethylammonium bromide, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of L-ascorbic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 60 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0066] (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0067] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0068] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL ethyl acetate and stirred for 1h; the dispersed solution was added to the silicone pressure-sensitive adhesive and stirred for 1h, and coated on a PET substrate using a wire rod coating process. The coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based antistatic film. The surface resistance of the nano bacterial cellulose-based antistatic film is 2.6×10 7 Ω.
[0069] Example 3
[0070] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0071] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0072] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0073] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropylmethyldimethoxysilane was added and modified for 9 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0074] (2) 100 mL of 0.1 mol / L glyoxylic acid solution and 10 mL of 0.15 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 45 min to obtain a nano bacterial cellulose reduced solution.
[0075] (3) In a constant temperature water bath at 30°C, 100 mL of 0.1 mol / L silver nitrate solution, 0.5 g of sodium dodecylbenzene sulfonate, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of glyoxylic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 30 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0076] (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0077] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0078] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL cyclohexane and stirred for 1h; the dispersed solution was added to the silicone pressure-sensitive adhesive and stirred for 1h, and coated on a PET substrate using a wire rod coating process. The coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based antistatic film. The surface resistance of the nano bacterial cellulose-based antistatic film is 3.1×10 6 Ω.
[0079] Example 4
[0080] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0081] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0082] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0083] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropyltrimethoxysilane was added and modified for 12 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0084] (2) 100 mL of 0.05 mol / L sodium borohydride solution and 10 mL of 0.5 mol / L ammonia water were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 45 min to obtain a nano bacterial cellulose reduced solution.
[0085] (3) In a constant temperature water bath at 30°C, 50 mL of 0.05 mol / L copper sulfate solution, 0.5 g of polyvinyl pyrrolidone, ethanol and polyethylene glycol 200 were mixed evenly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of sodium borohydride solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 30 minutes to obtain nano-copper particles by in situ reduction on the nanobacterial cellulose matrix.
[0086] (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0087] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0088] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL of ethanol and isopropanol, and stirred and dispersed for 1h; the dispersed solution was added to the polyurethane resin, stirred and dispersed for 1h, and coated on a flexible PI substrate using a doctor blade coating process, and the coated substrate was placed in a 150°C oven for curing for 1min to obtain a nano bacterial cellulose-based stretchable electrode material. The conductivity of the nano bacterial cellulose-based stretchable electrode material is 0.16S / m, the specific capacitance is 577F / g at a current density of 1A / g, and the stress-strain is 93MPa.
[0089] Example 5
[0090] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0091] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0092] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0093] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropylmethyldiethoxysilane was added and modified for 6 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0094] (2) 100 mL of 0.08 mol / L L-ascorbic acid solution and 10 mL of 0.1 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 60 min to obtain a nano bacterial cellulose reduced solution.
[0095] (3) In a constant temperature water bath at 30°C, 50 mL of 0.08 mol / L copper sulfate solution, 0.5 g of hexadecyltrimethylammonium bromide, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added to each liter of L-ascorbic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 60 minutes to obtain nano-copper particles by in situ reduction on the nanobacterial cellulose matrix.
[0096] (4) The solution after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0097] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0098] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL of ethyl acetate and stirred for 1h; the dispersed solution was added to the polyurethane resin and stirred for 1h, and coated on a flexible PI substrate using a blade coating process, and the coated substrate was placed in a 150°C oven for curing for 1min to obtain a nano bacterial cellulose-based stretchable electrode material. The conductivity of the nano bacterial cellulose-based stretchable electrode material is 0.19S / m, the specific capacitance is 636F / g at a current density of 1A / g, and the stress-strain is 98MPa.
[0099] Example 6
[0100] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0101] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0102] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0103] 0.5 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and ultrasonically dispersed for 3.0 h. Then, 1 mL of 3-aminopropylmethyldimethoxysilane was added and modified for 9 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 1.0 wt.%.
[0104] (2) 100 mL of 0.1 mol / L glyoxylic acid solution and 10 mL of 0.15 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 45 min to obtain a nano bacterial cellulose reduced solution.
[0105] (3) In a constant temperature water bath at 30°C, 50 mL of 0.1 mol / L copper sulfate solution, 0.5 g of sodium dodecylbenzene sulfonate, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of glyoxylic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 30 minutes to obtain nano-copper particles by in situ reduction on the nanobacterial cellulose matrix.
[0106] (4) The solution after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0107] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0108] 0.25g of nano bacterial cellulose conductive filler was added to a mixed solution of 5mL of ethyl acetate and stirred for 1h; the dispersed solution was added to the polyurethane resin and stirred for 1h, and coated on a flexible PI substrate using a blade coating process, and the coated substrate was placed in a 150°C oven for curing for 1min to obtain a nano bacterial cellulose-based stretchable electrode material. The conductivity of the nano bacterial cellulose-based stretchable electrode material is 0.22S / m, the specific capacitance is 687F / g at a current density of 1A / g, and the stress-strain is 113MPa.
[0109] Example 7
[0110] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0111] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0112] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0113] 5.0 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and high-pressure homogenization was performed for 3.0 h. Then, 2 mL of 3-aminopropyltrimethoxysilane was added and modified for 12 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 10.0 wt.%.
[0114] (2) 100 mL of 0.1 mol / L sodium borohydride solution and 10 mL of 0.15 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 60 min to obtain a nano bacterial cellulose reduced solution.
[0115] (3) In a constant temperature water bath at 30°C, 100 mL of 0.1 mol / L silver nitrate solution, 2.5 g of polyvinyl pyrrolidone, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of sodium borohydride solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 60 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0116] (4) The solution after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0117] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0118] 1.0g of nano bacterial cellulose conductive filler was added to a mixed solution of 10mL of ethanol and isopropanol, and stirred and dispersed for 1h; the dispersed solution was added to the silicone pressure-sensitive adhesive, and stirred and dispersed for 1h, and coated on a PET substrate by a spraying process, and the coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based electromagnetic shielding film. The shielding effectiveness of the nano bacterial cellulose-based electromagnetic shielding film is 48dB.
[0119] Example 8
[0120] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0121] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0122] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0123] 5.0 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and subjected to high-pressure homogenization for 3.0 h. Then, 2 mL of 3-aminopropylmethyldiethoxysilane was added and modified for 6 h to obtain a pretreated bacterial cellulose dispersion with a concentration of 10.0 wt.%.
[0124] (2) 100 mL of 0.04 mol / L L-ascorbic acid solution and 10 mL of 0.5 mol / L ammonia water were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 60 min to obtain a nano bacterial cellulose reduced solution.
[0125] (3) In a constant temperature water bath at 30°C, 100 mL of 0.04 mol / L silver nitrate solution, 2.5 g of hexadecyltrimethylammonium bromide, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of L-ascorbic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 60 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0126] (4) The solution after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0127] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0128] 1.0g of nano bacterial cellulose conductive filler was added to a mixed solution of 10mL of ethyl acetate, and stirred and dispersed for 1h; the dispersed solution was added to an organic silicone pressure-sensitive adhesive, and stirred and dispersed for 1h, and the solution was coated on a PET substrate by a spraying process, and the coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based electromagnetic shielding film. The shielding effectiveness of the nano bacterial cellulose-based electromagnetic shielding film is 53dB.
[0129] Example 9
[0130] A method for preparing a nano bacterial cellulose conductive filler comprises the following steps:
[0131] (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion:
[0132] The nano bacterial cellulose was fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it was immersed in a 0.1 mol / L NaOH solution, heated to 85°C, and boiled for 90 minutes to wash out the culture medium and bacteria remaining inside the particles, and then rinsed with a 0.3 wt.% CH3COOH solution to neutralize it to a pH of 7.2, and finally rinsed with deionized water to obtain purified nano bacterial cellulose;
[0133] 5.0 g of purified bacterial cellulose was added to a mixed solution of 50 mL of deionized water and ethanol, and subjected to high pressure homogenization for 3.0 h. Then, 2 mL of 3-aminopropylmethyldimethoxysilane was added and modified for 9 h to obtain a pretreated bacterial cellulose dispersion having a concentration of 10.0 wt.%.
[0134] (2) 100 mL of 0.075 mol / L glyoxylic acid solution and 10 mL of 0.075 mol / L NaOH solution were mixed and stirred to obtain a mixed solution, which was added to the pretreated bacterial cellulose dispersion and stirred for 60 min to obtain a nano bacterial cellulose reduced solution.
[0135] (3) In a constant temperature water bath at 30°C, 100 mL of 0.075 mol / L silver nitrate solution, 2.5 g of sodium dodecylbenzene sulfonate, ethanol and polyethylene glycol 200 were mixed uniformly to obtain a mixed solution; wherein, 100 mL of ethanol and 15 mL of polyethylene glycol 200 were added per liter of glyoxylic acid solution; the mixed solution was added dropwise to the nanobacterial cellulose reduction solution through a peristaltic pump at 100 rpm, and the reaction was stirred for 60 minutes to obtain nanosilver particles by in situ reduction on the nanobacterial cellulose matrix.
[0136] (4) The solution after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
[0137] The nano bacterial cellulose conductive filler is used to prepare a nano bacterial cellulose-based conductive composite film material, and the method comprises the following steps:
[0138] 1.0g of nano bacterial cellulose conductive filler was added to a mixed solution of 10mL of cyclohexane, and stirred and dispersed for 1h; the dispersed solution was added to an organic silicone pressure-sensitive adhesive, and stirred and dispersed for 1h, and the solution was coated on a PET substrate by a spraying process, and the coated substrate was placed in a 160°C oven for curing for 2min to obtain a nano bacterial cellulose-based electromagnetic shielding film. The shielding effectiveness of the nano bacterial cellulose-based electromagnetic shielding film is 57dB.
Claims
1. A nano bacterial cellulose conductive filler, characterized in that: The conductive filler is prepared by using nano bacterial cellulose as a matrix material and in-situ reduction deposition of nano copper particles or nano silver particles on the three-dimensional network structure of the conductive filler.
2. The method for preparing the nano bacterial cellulose conductive filler according to claim 1, characterized in that: The specific steps include: (1) Pretreatment and purification of nano bacterial cellulose and preparation of dispersion: After purifying the nano bacterial cellulose, modify and disperse it to obtain a pretreated nano bacterial cellulose dispersion; (2) mixing the alkaline solution and the reducing agent and stirring them uniformly to obtain a mixed solution, adding the mixed solution to the pretreated nano bacterial cellulose dispersion and stirring them uniformly to obtain a nano bacterial cellulose reduced solution; (3) under constant temperature conditions, mixing and stirring a copper ion solution or a silver ion solution, a dispersant and a stabilizer to obtain a mixed solution, then dropping the mixed solution into a nano bacterial cellulose reduction solution, stirring and reacting for a period of time, and in-situ reducing the nano bacterial cellulose on the nano bacterial cellulose matrix to obtain nano copper particles or nano silver particles; (4) The product after the reaction in step (3) is washed with deionized water and dried to obtain a nano bacterial cellulose conductive filler.
3. The method for preparing the nano bacterial cellulose conductive filler according to claim 2, characterized in that: In the step (1), the purification process of the nano bacterial cellulose is as follows: the nano bacterial cellulose is fully rinsed with deionized water to remove the culture medium and impurities remaining on the surface; then it is immersed in an alkaline solution, heated and boiled to wash out the culture medium and bacteria remaining inside the particles, then rinsed with an acid solution for neutralization, and finally rinsed with deionized water to obtain the purified nano bacterial cellulose; The alkaline solution is a 0.05-0.2 mol / L NaOH solution, heated at 75-95°C, and boiled for 60-120 min; The acid solution is a 0.1-0.5 wt. % CH3COOH solution, which is rinsed to a pH of 6.8-7.
2.
4. The method for preparing the nano bacterial cellulose conductive filler according to claim 2, characterized in that: In the step (1), the modified dispersion process of the purified nano bacterial cellulose is as follows: adding the purified nano bacterial cellulose into a solvent for dispersion treatment, and then adding a modifier for chemical modification to obtain a pretreated bacterial cellulose dispersion; The solvent is one or two of deionized water, ethanol, and isopropanol. When two solvents are selected, the ratio between the two solvents is arbitrary; the mass ratio of cellulose to solvent is 1: (10-100); The dispersion treatment method is a mixed treatment method of one or more of mechanical stirring, ultrasonic dispersion, high-pressure homogenization, and centrifugal dispersion, and the dispersion treatment time is 0.5 to 3.0 hours; The modifier is selected from one or more of dopamine, 3-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-β-(aminoethyl)γ-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane and N-β-(aminoethyl)γ-aminopropylmethyldiethoxysilane. When multiple modifiers are mixed, the multiple modifiers can be in any proportion. The volume ratio of the modifier to the solvent is 1:(25-50), and the modification time is 6-12 hours. The concentration of the pretreated bacterial cellulose dispersion is 0.1-40 wt.%.
5. The method for preparing the nano bacterial cellulose conductive filler according to claim 2, characterized in that: In the step (2), the alkaline solution is a sodium hydroxide solution or aqueous ammonia, the concentration of the sodium hydroxide solution is 0.05-0.15 mol / L, and the concentration of the aqueous ammonia is 0.5 mol / L; The reducing agent is one or two of sodium borohydride, glyoxylic acid, glucose, potassium sodium tartrate, L-ascorbic acid and sodium citrate. When two reducing agents are selected, the molar ratio of the two is 1:1; the concentration of the reducing agent is 0.02-0.1 mol / L; The volume ratio of the pretreated nano bacterial cellulose dispersion, the alkaline solution and the reducing agent is 5:(1-5):(1-10), and the stirring time is 30-60 minutes.
6. The method for preparing the nano bacterial cellulose conductive filler according to claim 2, characterized in that: In the step (3), the constant temperature condition is 10-60° C., the concentration of the copper ion solution or the silver ion solution is 0.02-0.1 mol / L, and the volume ratio of the copper ion solution or the silver ion solution to the nano bacterial cellulose reducing solution is 1:(1-5); wherein the copper ion solution is selected from one of a copper sulfate aqueous solution, a copper chloride aqueous solution and a copper nitrate aqueous solution, and the silver ion solution is a silver nitrate solution or a silver amine complex solution; The silver amine complex solution is one of a silver amine oxalate complex solution, a silver amine acetate complex solution, a silver amine malonate complex solution, a silver amine tartrate complex solution, a silver amine citrate complex solution and a silver amine neodecanoate complex solution; The amount of the dispersant is 0.5 to 1.0 times the mass of the nano bacterial cellulose, and is selected from one or more of polyvinyl pyrrolidone, polyethylene glycol, hexadecyltrimethylammonium bromide and sodium dodecylbenzene sulfonate. When multiple dispersants are mixed, the multiple dispersants are in any proportion; The stabilizers are ethanol and polyethylene glycol 200, both of which are analytically pure. The amount of stabilizer added is 50-100 mL of ethanol and 10-20 mL of polyethylene glycol 200 per liter of reducing agent. The mixed solution is added to the nano bacterial cellulose reducing solution at a speed of 100 rpm through a peristaltic pump, and the reaction time is 30-120 minutes.
7. The use of the nano bacterial cellulose conductive filler according to claim 1, characterized in that: Specifically, it is used for the preparation of nanobacterial cellulose-based conductive composite film materials, including nanobacterial cellulose-based antistatic films, nanobacterial cellulose-based electromagnetic shielding films and nanobacterial cellulose-based stretchable electrode materials.
8. The method for preparing the nano bacterial cellulose-based conductive composite film material according to claim 7, characterized in that: The specific steps include: The nano bacterial cellulose conductive filler is added into a solvent and dispersed evenly, and then added into a polymer material, stirred evenly and then thermally cured to obtain a nano bacterial cellulose-based conductive composite film material.
9. The method for preparing the nano bacterial cellulose-based conductive composite film material according to claim 8, characterized in that: The mass ratio of the nano bacterial cellulose conductive filler to the solvent is (0.1-1.0):10; the solvent is selected from one or two of ethanol, isopropanol, cyclohexane and ethyl acetate, all of which are analytically pure. When two solvents are selected, the two solvents are in any ratio; the dispersion treatment method is a mixed treatment of one or more of mechanical stirring, ultrasonic dispersion, high pressure homogenization and centrifugal dispersion, and the dispersion treatment time is 0.5-1.0h; The polymer material is one of a release agent, a pressure-sensitive adhesive and a hardening resin; the release agent is a silicone release agent, the pressure-sensitive adhesive is one of an organic silicone pressure-sensitive adhesive, an acrylate pressure-sensitive adhesive and a rubber pressure-sensitive adhesive, and the hardening resin is one of an epoxy resin, an acrylic resin, a polyurethane resin, an acrylic modified polyurethane resin and a propylene oxide resin; the stirring time is 0.5 to 1.0 h; The thermal curing is specifically performed in an oven at a temperature of 150 to 200° C. for a curing time of 1 to 5 minutes.
10. The nano bacterial cellulose-based conductive composite film material according to claim 7, characterized in that: The surface resistance of the nano bacterial cellulose based antistatic film is 10 5 ~10 8 Ω; the shielding effectiveness of the nanobacterial cellulose-based electromagnetic shielding film is 45-60dB; the conductivity of the nanobacterial cellulose-based stretchable film electrode material is 0.1-0.5S / m, the specific capacitance is 400-800F / g at a current density of 1A / g, and the stress-strain is 80-150MPa.
Citation Information
Patent Citations
Nitrogen-doped carbonized bacterial cellulose loaded nano-platinum electrode material and preparation method thereof
CN106299385A
Preparation method of bacterial cellulose / polyaniline / gold nanoparticle composite material
CN112094437A
Cited By
Preparation process of high-dispersity silver powder
CN122322496A
